Job Changes and Interregional Migration of Graduates - Tina Haußen; Tina Haussen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We empirically analyze job changes and related location choices for graduates in Germany and its determinants. Using a longitudinal, representative survey-based dataset, we not only observe the transition of graduates to the labor market but also every subsequent job change within five years after graduation. Contrary to what is often assumed in the literature, our findings show that around 75% of the graduates have more than one job within our observation period and for a non-negligible share of them, job changes are related to interregional migration. Whereas job changes mostly depend on the field of study and previous employment conditions, migration is predominantly affected by previous migration paths and regional characteristics.
Keywords: J61; R11; I23; 330